Regulation of Oxidative Stress by Long Non-coding RNAs in Central Nervous System Disorders - Xu, Xiaoman; Zhang, Yi (Frontiers in Molecular Neuroscience, 2022)
Central nervous system (CNS) disorders, such as ischemic stroke, Alzheimer's disease, Parkinson's disease, spinal cord injury, glioma, and epilepsy, involve oxidative stress and neuronal apoptosis, often leading to long-term disability or death. Emerging studies suggest that oxidative stress may induce epigenetic modifications that contribute to CNS disorders. Non-coding RNAs are epigenetic regulators involved in CNS disorders and have attracted extensive attention. Long non-coding RNAs (lncRNAs) are non-coding RNAs more than 200 nucleotides long and have no protein-coding function. However, these molecules exert regulatory functions at the transcriptional, post-transcriptional, and epigenetic levels. However, the major role of lncRNAs in the pathophysiology of CNS disorders, especially related to oxidative stress, remains unclear. Here, we review the molecular functions of lncRNAs in oxidative stress and highlight lncRNAs that exert positive or negative roles in oxidation/antioxidant systems. This review provides novel insights into the therapeutic potential of lncRNAs that mediate oxidative stress in CNS disorders.